Comparative Study on Aggression among Persons Deprived of their Liberty: Array - Popa, Ecaterina; Munteanu (Moisa), Valentina Beatrice (New Trends in Psychology, 2020)
The article is a comparative study that aims to highlight the role of aggression among persons deprived of liberty, to identify the psychological mechanisms involved in their aggressive behavior, as well as the psychological consequences on their personality. Notions such as aggression, violence, personality and human behavior are extremely complex, which is why it requires great attention in addressing various theoretical, contextual, individual, group, institutional, legislative and moral perspectives. The article aims to observe the changes that occur from a behavioral point of view in both young people and adults in prison.